2012
DOI: 10.1117/1.jbo.17.3.037007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diffuse correlation spectroscopic measurement of cerebral blood flow using phase-encoded velocity mapping magnetic resonance imaging

Abstract: Abstract. Diffuse correlation spectroscopy (DCS) is a novel optical technique that appears to be an excellent tool for assessing cerebral blood flow in a continuous and non-invasive manner at the bedside. We present new clinical validation of the DCS methodology by demonstrating strong agreement between DCS indices of relative cerebral blood flow and indices based on phase-encoded velocity mapping magnetic resonance imaging (VENC MRI) of relative blood flow in the jugular veins and superior vena cava. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 38 publications
3
86
3
Order By: Relevance
“…This observation agrees with our previous experience in healthy adults 20 and with several other publications that examined cerebrovascular reactivity to hypercapnia in patients with congenital heart defects using localized measurement techniques, such as DOS and DCS. 15,24,38 In addition to generating new physiologic data, this work also achieved several technical goals. First, it demonstrates the feasibility of a combined MRI-susceptometry and phase-contrast method to measure S v O 2 , CBF and CMRO 2, in neonates with complex CHD, all in absolute physiologic units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation agrees with our previous experience in healthy adults 20 and with several other publications that examined cerebrovascular reactivity to hypercapnia in patients with congenital heart defects using localized measurement techniques, such as DOS and DCS. 15,24,38 In addition to generating new physiologic data, this work also achieved several technical goals. First, it demonstrates the feasibility of a combined MRI-susceptometry and phase-contrast method to measure S v O 2 , CBF and CMRO 2, in neonates with complex CHD, all in absolute physiologic units.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that changes of BFI relative to a baseline are strongly correlated with changes in CBF relative to baseline values measured by other CBF techniques. 15,21,24 Diffuse Optical Spectroscopy and Diffuse Correlation Spectroscopy Instrumentation and Study Protocol A schematic of the measurement protocol is provided in Figure 1, and further details are given in Appendix 1. First, baseline DOS measurements of absolute tissue physiologic parameters, i.e., HbR, HbO 2 , THC, and StO 2 were made on the patient's forehead while the subject was sedated, stabilized, and while vascular access was obtained outside the MRI scanner.…”
Section: Magnetic Resonance Imaging Measurementsmentioning
confidence: 99%
“…In fact, DCS CBF i correlates well with MR arterial spin labeling 38 and with phase-encoded velocity mapping (VENC) MRI measures of relative blood flow in the jugular veins and superior vena cava in neonates/children with congenital heart defect. 39 Further support for the use of DCS CBF i measures was provided by the high correlation (r 2 ¼ 0.73, Po0.01) between relative CBF i and Xenon CT cerebral blood perfusion measures in critically brain-injured adults. 40 These comparisons show that CBF i measured by DCS offers reasonable agreement with other modalities, in particular those providing perfusion measurements, and therefore provides a reliable index of CMRO 2 .…”
Section: Indices Of Cerebral Oxygen Metabolism and Cerebral Blood Flowmentioning
confidence: 99%
“…We then fit the diffusion correlation equation to the measured autocorrelation function, acquired sequentially, about once per second, to obtain the blood flow index (CBF i ) 10,11 . DCS measures of blood flow changes have been extensively validated 12,13 . By combining the FDNIRS measures of SO 2 with the DCS measures of CBF i , we achieve an estimate of cerebral oxygen metabolism (CMRO 2i ).…”
Section: Introductionmentioning
confidence: 99%